Polymer‐Supported Liquid Layer Electrolyzer Enabled Electrochemical CO2 Reduction to CO with High Energy Efficiency. Issue 6 (8th June 2021) - Li, Shangyu; Ma, Yiwen; Zhao, Tiancheng; Li, Jiaxin; Kang, Xinyue; Guo, Wen; Wen, Yunzhou; Wang, Liping; Wang, Yurui; Lin, Renxing; Li, Tiantian; Tan, Hairen; et al.
Abstract: The electrochemical conversion of carbon dioxide (CO2 ) to carbon monoxide (CO) is a favorable approach to reduce CO2 emission while converting excess sustainable energy to important chemical feedstocks. At high current density (>100 mA cm −2 ), low energy efficiency (EE) and unaffordable cell cost limit the industrial application of conventional CO2 electrolyzers. Thus, a crucial and urgent task is to design a new type of CO2 electrolyzer that can work efficiently at high current density. Here we report a polymer‐supported liquid layer (PSL) electrolyzer using polypropylene non‐woven fabric as a separator between anode and cathode. Ag based cathode was fed with humid CO2 and potassium hydroxide was fed to earth‐abundant NiFe‐based anode. In this configuration, the PSL provided high‐pH condition for the cathode reaction and reduced the cell resistance, achieving a high full cell EE over 66 % at 100 mA cm −2 . Abstract : A polymer‐supported liquid layer electrolyzer is reported for electrochemical CO2 reduction. We have achieved a low cell voltage of 2 V and an energy efficiency of 66 % at the current density of 100 mA cm −2 .